Valley-filling Potential Evaluation of Urban Public Charging Stations Based on Price Incentive - Dawei SU; Yihui FAN; Tianhui ZHAO; Hongjin PAN; Youhui HUANG; Gang WANG; Yongyong JIA (Zhongguo dianli)
With large scale integration of renewable energy, motivating valley-filling users to participate in power grid regulation to tap the valley-filling potential of charging loads has become one of the important means to enhance the space for renewable energy consumption. Firstly, an evaluation framework for valley-filling potential of urban public charging stations is built in this paper. Probability modeling is conducted on charging orders, and a random sampling-based Monte Carlo simulation is carried out to obtain the sampling data representing the starting charging time. Then, the typical load characteristic indicators including valley-period and flat-period load rates are proposed, and the charging load valley-filling potential evaluation parameters are introduced to carry out valley-filling potential evaluation of urban public charging stations. Finally, based on the actual charging order data of the urban charging stations in a pilot city under different price incentives, a quantitative evaluation of the valley-filling potential of urban public charging stations is carried out. The results show that the simulated charging load is consistent with the actual load in tendency, and the change pattern is similar to the actual situation. When the service fee discount exceeds 30%, for every additional 10% discount, the average valley-filling response will increase by approximately 23.6 MW. Therefore, the proposed evaluation framework realizes the quantification of valley filling potential of public charging stations.